2020
DOI: 10.1136/bmjopen-2019-034370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teaching unit design: a realist systematic review protocol of evidence-based practices for clinical education and health service delivery

Abstract: IntroductionThe clinical teaching unit (CTU) has emerged as a near-ubiquitous model of clinical education across Canadian and international medical schools since it was first proposed over 50 years ago. However, while healthcare has changed dramatically over this period, the CTU model has remained largely unchanged. We thus aimed to systematically review principles of CTU design that contribute to improved outcomes in clinical education and health service delivery.Methods and analysisWe will perform a realist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In total, we con sidered 2464 studies after removing duplicates; 358 articles underwent fulltext review, of which 262 articles met inclusion criteria. Given the range of clinical specialties represented in included studies (Appendix 1, Section 3, Supplementary Table 1), as determined a priori, 5 we limited data analysis to studies from general internal medicine CTUs to limit contextual variability. Therefore, we included 107 studies in our analysis, which are summarized in Table 1 and described in detail in Appendix 1, Section 3, Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we con sidered 2464 studies after removing duplicates; 358 articles underwent fulltext review, of which 262 articles met inclusion criteria. Given the range of clinical specialties represented in included studies (Appendix 1, Section 3, Supplementary Table 1), as determined a priori, 5 we limited data analysis to studies from general internal medicine CTUs to limit contextual variability. Therefore, we included 107 studies in our analysis, which are summarized in Table 1 and described in detail in Appendix 1, Section 3, Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Two reviewers (B.T., R.S., J.C., K.A.D., K.R.D., S.S.) independently extracted data from each included study using a standardized, prepiloted form. 5 Two reviewers (B.T., R.S., J.C., K.A.D., K.R.D.) independently assessed methodological quality for all studies, using the Medical Education Research Study Quality Instrument (MERSQI) 6 for quantitative studies and the Consolidated Criteria for Reporting Qualitative Research (COREQ) instrument 7 for qualitative studies.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…medical students and resident physicians) directly involved in patient care under the supervision of an internist acting as the most responsible practitioner (MRP). 21 While some literature has found similar overall costs for resource utilization between teaching and non-teaching units, other studies have suggested slightly higher overall costs associated with teaching hospitals, as well as higher isolated costs for laboratory and radiographic testing within teaching units. 22,23 Conducting our analysis within this setting provides useful insights into factors affecting laboratory test utilization with a degree of external validity within other academic structures similar to CTUs.…”
Section: Introductionmentioning
confidence: 99%
“…6 The attending physician serves as the most responsible physician for patient care, while simultaneously teaching learners of various skill levels and leading multidisciplinary teams of health care providers. 7 The attending physicians instruct and act as role models for the future physician workforce. 8 This role requires the execution of professional competence and is vulnerable to several unpredictable contextual factors.…”
mentioning
confidence: 99%